2006
DOI: 10.1007/s10815-005-9019-8
|View full text |Cite
|
Sign up to set email alerts
|

Gn-RH antagonists in intrauterine insemination: the weekend-free protocol

Abstract: Objective:To compare the results of intrauterine insemination (IUI) when GnRH antagonist was added-to avoid IUI on weekend-with those obtained with the standard IUI protocol. Study design:In an IUI program under ovarian stimulation with gonadotropins when one or more follicles of 15-16 mm were seen, if it was not possible for logistic reasons (weekend) to perform the insemination 72 h later, GnRH antagonist was administered until human chorionic gonadotropin (hCG) administration. The IUI was performed on Monda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 16 publications
(18 reference statements)
4
21
1
2
Order By: Relevance
“…All of the other RCTs reported that multiple pregnancies observed were only twins. The retrospective study (8) reported equal number of high-order multiple pregnancies in both groups.…”
Section: Meta-analysis: Main Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…All of the other RCTs reported that multiple pregnancies observed were only twins. The retrospective study (8) reported equal number of high-order multiple pregnancies in both groups.…”
Section: Meta-analysis: Main Resultsmentioning
confidence: 90%
“…Also an analysis that included the retrospective trial of Matorras et al (8) was performed. Data extraction was performed independently by two investigators ,and conflicts were solved after discussion.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…(23,24) The use of GnRH antagonists has also been shown to be effective in manipulating follicular development, so that the insemination process can be suspended on weekends without an apparent decrease in pregnancy rates. (25,26) The present study was not without limitations. The number of women enrolled in the study small; nevertheless, other studies investigating the same subject have also enrolled small numbers of patients.…”
Section: Discussionmentioning
confidence: 85%
“…Apart from a particular subgroup of patients, routine application of antagonists will only increase the cost treatment without any effect on pregnancy rate. ESHRE Capri Workshop also stated discharges and therefore fail to complete treatment; * cycles initiated with the intention to proceed to IUI but switched to ART; * when one or more follicles measure ≥14 mm and the probable day of insemination coincide weekend; in order to skip the weekend for logistic reasons or the lack of on call staff (31) and * To decrease the frequency of sonography examinations and blood hormone measurements and related clinical task burden.…”
Section: Discussionmentioning
confidence: 99%